Computation of Shock Profiles in Radiative Hydrodynamics (Communications in Computational Physics, 2020)
This article is devoted to the construction of a numerical scheme to solve theequations of radiative hydrodynamics. We use this numerical procedure to computeshock profiles and illustrate some earlier theoretical results about their smoothnessand monotonicity properties. We first consider a scalar toy model, then we extend ouranalysis to a more realistic system for the radiative hydrodynamics that couples theEuler equations and an elliptic equation.